The Evaluation of PMP22 and Protein 0, Examinations for Early Disability Detection in Leprosy Patients - Dhelya Widasmara, - (Hiroshima University Medical Press, 2018)
Introduction: Leprosy is a chronic infectious disease caused by Mycobacterium leprae that has a predilection for peripheral nerves, especially Schwann cells. Leprosy medications may only eradicate the bacteria without preventing or recovering peripheral nerve damage. Previous studies proved that Krox-20 could be a useful diagnostic tool for early peripheral nerve damage detection in leprosy.nObjective: To analyse and to determine PMP22, and P0 cut-off points as diagnostic tools of early disability in leprosy. Methods: We examined ambulatory patients at Kediri Leprosy Hospital, Indonesia. We employed WHO’s criteria to assess the degree of disability and measured the study variables using ELISA. We then determine the cut-off value using Receiver Operating Characteristic curve. Results: From overall patients (n=79), 36 patients had 0-degree of disability, and 43 patients had 1-degree of disability. The ROC curve analysis revealed cut-off values for PMP22 and P0 at 4,42 pg/mL and 11,39 pg/mL, respectively. The mean value for all variables in patients with 0-degree of disability were higher than that in patients with 1-degree of disability at 12,56 pg/mL vs 4,24 pg/mL (p<0,05) and at 9,85 pg/mL vs 2,86 pg/mL, respectively (p<0,05). Conclusion: Leprosy is a chronic infectious disease that brings forth many degrees of disability secondary to peripheral nerve invasion, particularly Schwann cells. Hence, early detection of peripheral nerve damage becomes crucial. The evaluation of PMP22 and P0 examinations is useful to identify early peripheral nerve damage in leprosy.